Effect of Healthcare Service Quality and Price on Patient Satisfaction - Sumardika, Aldian; Razak, Ismail; Yuaniko, Yuaniko (Marketing and Business Strategy, 2024)
Healthcare services is a place that is needed by all levels of society. Good service will influence patient satisfaction. Patient satisfaction in health services is very important to pay attention to because it can describe the quality of service at the health service location. Knowing patient satisfaction is very useful for the relevant agencies in order to evaluate programs that are being implemented and to find which parts need improvement. This study aims to analyze the influence of service quality and price on patient satisfaction at Kartika Husada Jatiasih Hospital. This type of research is a survey. The analytical method used in this research uses linear and multiple regression analysis models. The research results show that service quality has a positive and significant effect on patient satisfaction at Kartika Husada Jatiasih Hospital. Price has a positive and significant effect on patient satisfaction at Kartika Husada Jatiasih Hospital. Service quality and price have a positive and significant effect on patient satisfaction at Kartika Husada Jatiasih Hospital. Managerial implications include holding regular training for all hospital staff and implementing an effective feedback system to get input from patients about the quality of service